ANALYSIS OF INFRASTRUCTURE EFFECT ON INDONESIA'S ECONOMIC GROWTH YEAR 2007 - 2014 - Irawan, Rismanto; Iskandar, Deden Dinar (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
A production process requires inputs to be used to produce output. The input according to Solow is the capital and labor described in the Cobb – Douglas function. Infrastructure can be said as capital in an effort to increase productivity, since labor requires supporting facilities that can increase their productivity. Therefore infrastructure is seen as having an important role in driving economic growth, so that adequate infrastructure is expected to have a positive impact on economic growth. This study aims to analyze the influence of the availability of infrastructure that is divided into economic infrastructure, social infrastructure and institutional infrastructure, on the economy in Indonesia which is described by the GDP. This study uses secondary data in 33 provinces in Indonesia in 2007-2014. This study uses panel data regression using the fixed effect model and correction of Heteroscedasticity and Autocorrelation Consistent (HAC). Based on the results of econometric regression, it is known that the variables of road, electricity, education, health and capital expenditure have a positive and significant effect. While the employee expenditure variable has a positive but not significant relationship. In addition, it is known that telephone variables have a negative and insignificant relationship. The results of this study also show that electricity infrastructure has the biggest influence on economic growth..